Diseño y estructura del sistema de manejo de recursos humanos a través de tercerización, para empresas al sur de Quito. - Aguilar Sampedro, Natalia Vanessa (2007)
This dissertation is the pre-establishment of a service tercerizadora Human Resources in the city of Quito, with special interest in assisting Organizations southern city study.